Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s10535-015-0539-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of heat tolerance in crop plants

Abstract: Due to possible climate changes, heat stress has obtained a serious concern all over the world. Tolerance to this stress via knowledge of metabolic pathways will help us in engineering heat tolerant plants. A group of proteins called heat shock proteins are synthesized following stress and their synthesis is regulated by transcription factors. Under high temperature (HT), reactive oxygen species (ROS) are often induced and can cause damage to lipids, proteins, and nucleic acids. To scavenge the ROS and maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 81 publications
1
28
0
Order By: Relevance
“…Abiotic stresses, such as heat, drought, and salt, usually cause ROS production and membrane lipid peroxides, leading to the increase of membrane permeability and electrolyte leakage rate (Quinn 1988, Iba 2002, Cramer et al 2011. Malondialdehyde content and REC are important traits and could present the level of membrane lipid peroxides and membrane permeability, respectively (Asthir 2015). An increased membrane permeability and electrolyte leakage rate in Chinese cabbage have been identified under heat stress (Luo et al 1996, Ye et al 1996.…”
Section: Resultsmentioning
confidence: 99%
“…Abiotic stresses, such as heat, drought, and salt, usually cause ROS production and membrane lipid peroxides, leading to the increase of membrane permeability and electrolyte leakage rate (Quinn 1988, Iba 2002, Cramer et al 2011. Malondialdehyde content and REC are important traits and could present the level of membrane lipid peroxides and membrane permeability, respectively (Asthir 2015). An increased membrane permeability and electrolyte leakage rate in Chinese cabbage have been identified under heat stress (Luo et al 1996, Ye et al 1996.…”
Section: Resultsmentioning
confidence: 99%
“…High temperature, above the optimal growth temperature, is a major stress factor that impacts on the whole life cycle of plants; Ca 2+ , crossing membrane into the cells via Ca 2+ channels, is implicated in the development of heat tolerance in plants (Gong et al, 1997;Wahid et al, 2007;Li et al, 2012;Asthir, 2015;Li H. et al, 2019;Serrano et al, 2019). Recently, the positive effect of Glu in heat tolerance had been found by , who first reported that in maize (Zea mays L.) seedlings treatment with Glu elevated the survival percentage of seedlings under heat stress.…”
Section: Heat Stressmentioning
confidence: 99%
“…Along with global warming, high temperature has already become a noticeable abiotic stress worldwide, and the mechanisms of high temperature injury and heat tolerance have attracted much attention (Wahid et al, 2007; Asthir, 2015; Hemmati et al, 2015). Christou et al (2011) found that pre-treatment of roots with NaHS effectively alleviated the decrease in leaf chlorophyll fluorescence, stomatal conductance and relative leaf water content in strawberry ( Fragaria x ananassa cv.…”
Section: H2s-induced Cross-adaptationmentioning
confidence: 99%